Female terminalia of lower Brachycera - II (Diptera). - Nagatomi, Akira; Iwata, Kunio (Contributions to Entomology = Beiträge zur Entomologie, 1978)
The female terminalia of Stratiomyidae, and the genus Heterostomus (probably Geonomyiidae)are described and illustrated. Twenty-six genera and 39 species are treated in this paper. Thus a total of 12 families, 61 genera, and 89 species belonging to the lower Brachycera are included in our previous reports (Nagatomi & Iwata 1976, and Iwata & Nagatomi 1976) and the present paper, although many genera of Stratiomyidae still remain unstudied with respect to the female terminalia.